2013
DOI: 10.3390/molecules18044544
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effects on 13C-NMR Chemical Shifts of 10-Hydroxybenzo[h]quinolines

Abstract: Deuterium isotope effects on 13C-NMR chemical shifts are investigated in a series of 10-hydroxybenzo[h]quinolines (HBQ’s) The OH proton is deuteriated. The isotope effects on 13C chemical shifts in these hydrogen bonded systems are rather unusual. The formal four-bond effects are found to be negative, indicating transmission via the hydrogen bond. In addition unusual long-range effects are seen. Structures, NMR chemical shifts and changes in nuclear shieldings upon deuteriation are calculated using DFT methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…The title compounds are synthesized and purified according to the already described procedures. 13,14 They are dissolved with a concentration in the order of 10 -4 M in acetonitrile of Uvasol quality (Merck). Fused silica cuvettes with a thickness of 1 mm are employed as sample cells.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The title compounds are synthesized and purified according to the already described procedures. 13,14 They are dissolved with a concentration in the order of 10 -4 M in acetonitrile of Uvasol quality (Merck). Fused silica cuvettes with a thickness of 1 mm are employed as sample cells.…”
Section: Sample Preparationmentioning
confidence: 99%
“…One of the most distinguished works about deuterium isotope effects on 13 C chemical shifts have been reported by Hansen et al , who worked on deuterium isotope effects on chemical shifts in intramolecular hydrogen‐bonded systems, especially resonance assisted hydrogen bonding . In those cases, it has been shown that the isotope effect may be transmitted across the hydrogen bonds and may affect the chemical shifts in hydrogen‐bonded systems .…”
Section: Introductionmentioning
confidence: 99%
“…In those cases, it has been shown that the isotope effect may be transmitted across the hydrogen bonds and may affect the chemical shifts in hydrogen‐bonded systems . Also the variable‐temperature nuclear magnetic resonance (NMR) study of the enol forms of benzoylacetones and corresponding isotope effect, deuterium isotope effects on 13 C chemical shifts of nitromalonamide, 10‐Hydroxybenzo[ h ]quinolines, enaminocarbonyl derivatives of Meldrum's and Tetronic acid, o ‐hydroxy Schiff bases by applying factor analysis and tautomerism of an intramolecular O‐H...O...H‐N‐charge of the 15 N labeled Schiff base 3‐carboxy‐5‐methyl‐salicylidenaniline have been studied by means of the 1 H and 15 N NMR spectroscopy . Deuterium isotope effects in 13 C NMR spectra of intramolecularly hydrogen‐bonded salicylaldehyde‐4‐phenylthiosemicarbazone has also been studied by means of NMR spectroscopy by Novak et al …”
Section: Introductionmentioning
confidence: 99%
“…According to the NMR results in N,N-dimethylformamide (DMF) the 7,9-dinitro derivative 3 is fully in the keto form. 23 The 1 H chemical shis in DMF-d 7 (H-2, Hx) of 1 (9.03, 14.80), 2 (9.15, 16.68) and 3 (9.48 and 19.87) give an estimate of 68% keto form of 2 under the assumption that HBQ is fully in the enol form and 3 exists as a keto form only. Unfortunately the interpretation of the UV-Vis spectra in DMF is not straightforward.…”
Section: Structures 1-3mentioning
confidence: 99%
“…In compounds 2 and 3, the ground and excited state proton transfer is investigated as a consequence of incorporating a strong electron acceptor(s), 23 while in compounds 4 and 5 the inuence of competitive processes takes our attention. In the case of 4, the incorporation of an azo group creates an alternative tautomeric route (azo-quinonehydrazone, Scheme 2) to the HBQ type proton transfer.…”
mentioning
confidence: 99%